Smoking and incidence and mortality of colorectal cancer - Parajuli, Ranjan (UiT The Arctic University of Norway, 2014)
Paper 1 of this thesis is not available in Munin: 1. Parajuli R, Bjerkaas E, Tverdal A, Selmer R, Le Marchand L, Weiderpass E, Gram IT.: 'The increased risk of colon cancer due to cigarette smoking may be greater in women than men', Cancer Epidemiology, Biomarkers and Prevention (2013), vol. 22(5):862-871. Available at http://dx.doi.org/10.1158/1055-9965.EPI-12-1351 Smoking is one of the most important causes of cancer and premature death worldwide. Two different reports, the most recent monograph published by International Agency for Research on Cancer (IARC) in 2012 and the Unites States Surgeon General’s report of 2014, concluded that smoking is risk factor for both colon and rectal cancer. In addition to being one of the most common cancers in Norway, mortality from colorectal cancer (CRC) is also high. The main aim of this thesis was to examine the association between smoking and CRC incidence and mortality overall and by gender. We examined the association between smoking and colon cancer by location and gender (Paper I), rectal cancer by gender (Paper II) and CRC mortality by subsite and gender (Paper III). The cohort included 652,792 Norwegians (49% men) recruited from four Norwegian health screening surveys. These surveys were conducted between 1972 and 2003: the Oslo study I (1972-1973), the Norwegian counties study (1974-1988), the 40 years cohort (1985-1999) and the Cohort of Norway (CONOR, 1994-2003). The participation rate for the different surveys varied from 56-88%. Women ever smokers had a 19% and men ever smokers had 8% increased risk of colon cancer. Furthermore, women ever smokers had an increased risk of proximal colon cancer compared to men ever smokers (Paper I). Ever smokers had an increased risk of rectal cancer at around 25% and the risk increased was similar for men and women (Paper II). Men and women ever smokers had a similar increased risk of CRC mortality of about 20%. The risk of rectal and proximal colon cancer mortality was most pronounced among men and women smokers, ...